Analisis Strategi Pengembangan Obyek Wisata Waduk Riam Kanan di Kabupaten Banjar - Subhan Abdilah; Noor Rahmini (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2020)
This study aims to (1) determine the internal and external factors of right cascadereservoir tourism development in the Banjar district, and (2) develop the right cascadereservoir area in the Banjar district. There were six respondents in this study who wereconsidered influential in determining village spending in Kayu Bawang Village, used in dataprocessing using the SWOT method. The research results show that the development of themost appropriate strategy is the S-O strategy (1) Increase Tourist Perception to visit thistourism object because this tourism location is very strategic and has beautiful naturalscenery and cold air. (2) Optimizing the role of the POKDARWIS (Tourism AwarenessGroup) of the Culture and Tourism Office of the Banjar District to promote these attractions.